Changes in the surface potential of Lactobacillus acidophilus under freeze-thawing stress - Fernandez Murga, María Leonor (2000)
The zeta potential of Lactobacillus acidophilux CRL 640, a measure of the net distribution of electrical charges on the bacterial surface, is a function of the glucose concentration in the growing media. With 2% glucose, cells in the stationary phase showed a zeta potential of -45 ± 2 mV. With these cells, the zeta potential after freezing and thawing decreased to -32 ± 2 mV and there was a decrease in viability. The changes in the surface potential correlated with damage to the cell surface as shown by electron microscopy. Freeze-thawed cells incubated in a rich medium recovered a zeta potential of -38 ± 2 mV without cell growth. L. acidophilus CRL 640 showed the same value of surface potential as control cells when they were frozen and thawed in 2 M glycerol.